Poligami sebagai Ibahah Bersyarat: Penalaran Hukum Islam dan Regulasi Negara dalam Kitab Undang-Undang Hukum Pidana Nasional - Muhammad Fawwaz Farhan Farabi; Mesraini Mesraini; Raihanah Abdullah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (National KUHP) marks a paradigm shift in Indonesian family law enforcement, specifically regarding unregistered polygamy. This paper investigates the constitutionality and theological legitimacy of criminalizing unauthorized polygamy under Articles 401, 402, and 403 of the new Penal Code. Using a normative-juridical method approach through Fiqh Siyasah (Islamic political jurisprudence), this research addresses the tension between religious validity (diyanatan) and state legality (qada’an). The study reveals that the state’s regulation does not prohibit the permissible (haram li al-mubah) but applies the doctrine of taqyid al-mubah (restriction of permissible acts) based on sadd al-dzari’ah (blocking the means to harm). The research introduces the concept of Conditional Ibahah arguing that court permission is not merely administrative but a substantive condition to ensure the maqasid (objective) of justice and protection of lineage (hifz al-nasl). The findings conclude that the criminal sanctions in the new Criminal Code are legitimate forms of ta'zir authorized by the ruler to protect the rights of the first wife and children from the latent injustice of underground polygamy.